Parenting Children with Hearing Impairment: The Milieu of Parents’ Practices and Experiences - Badzis, Mastura; Garba, Rabiu (UUM Press, 2019)
The birth of a child with hearing impairment imposes more parental demands than having a child without a disability. Parents have little concern about the holistic growth and development of their children with hearing disability. This study aspires to delineate the parental practice and experience in dealing with behavioral problems of their children with hearing-impairments in a Special School in Kano State, Nigeria. This study employed a qualitative case study design in which interviews and observation were used to collect the data. Purposeful sampling was utilized in selecting three fathers and three mothers of children with hearing impairment. Data was recorded, transcribed and thematically analyzed in which categories were identified and generated. The findings accentuated several major themes and categories of parental practice and their experiences, which have to do with counselling the children with hearing impairment. Parental experience includes the judgment of others in the family and based on the findings, the researchers provide discernments to parents, their children with hearing impairment, and the immediate community where such children live.